Experimental Study on Physical Characteristics of Deep Rocks at Different Depths in Songliao Basin. (12th May 2022) - Yang, Mingqing; He, Zhiqiang; Li, Cong; Yang, Bengao; Liu, Guikang; Fu, Chenghang; Wang, Tianyu; Wei, Zijie
Abstract : Deep earth science is the basic of deep resource exploitation, and the research on the physical and mechanical characteristics of deep rock is a research hotspot at present. In order to study the physical characteristics of deep rock at different depths, based on the cores at different depths of 4900-6830 m in Songke Well 2 (SK-2), Songliao Basin, this paper carried out the study including the rock characteristics of mineral, wave velocity, density, and pore, the variation law of physical characteristics of deep rock with depth is studied, and the relationship between different physical parameters of deep rocks is explored. It is found that the core composition minerals of SK-2 at the depth of 4900-6830 m vary greatly with the depth, in which the quality of hard phase minerals accounts for a large proportion. After entering the basement stratum, the mineral content of different phases tends to be close. With the increase of depth, the wave velocity, density, and dynamic elastic modulus of rocks show a linear increase trend, and there is a positive correlation between density and wave velocity. In the range of 4900-6830 m depth, the porosity generally shows a downward trend with the increase of depth. In the range of 6000-6830 m, the porosity tends to be close to 7% with the increase of depth, indicating that formation compaction has little impact on the development of igneous pores in this formation. There is a negative correlation between wave velocity and porosity, and the empirical formula is fitted. This study can provide a reference for the exploration of deep geoscience and deep engineering practice.